2013
DOI: 10.1038/bjc.2013.24
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting inflammation for therapeutic gain in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy associated with <5% 5-year survival, in which standard chemotherapeutics have limited benefit. The disease is associated with significant intra- and peritumoral inflammation and failure of protective immunosurveillance. Indeed, inflammatory signals are implicated in both tumour initiation and tumour progression. The major pathways regulating PDAC-associated inflammation are now being explored. Activation of leukocytes, and upregulation of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 51 publications
(58 reference statements)
1
80
0
Order By: Relevance
“…Recently, it was reported that tumorigenesis in the pancreas is associated with significant intra-and peri-tumoral inflammation and failure of protective immunosurveillance (75). Neutrophil activation and proliferation are indicative of TH-1 pathway of cell-mediated immunity involvement (76).…”
Section: Peripheral Blood Cellmentioning
confidence: 99%
“…Recently, it was reported that tumorigenesis in the pancreas is associated with significant intra-and peri-tumoral inflammation and failure of protective immunosurveillance (75). Neutrophil activation and proliferation are indicative of TH-1 pathway of cell-mediated immunity involvement (76).…”
Section: Peripheral Blood Cellmentioning
confidence: 99%
“…A genetic basis for some insulinomas has been linked to the gene for Multiple Endocrine Neoplasia I (MEN1) and k-ras mutations, however chronic inflammation is also known to be oncogenic and may contribute to the malignant transformation in many different types of tumors [12][13][14] . Toll-like receptors (TLR) are a family of cell surface pattern recognition receptors in immune cells which recognize signature molecules of different environmental pathogens and are important components of the innate and acquired immune system [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism is not entirely understood, sustained inflammation contributes to a compromised anti-tumor immune response via the infiltration of immunosuppressive regulatory T cells and MDSC (29,30). In addition, these inflammatory stimuli activate stellate cells and fibroblasts, leading to fibrotic remodeling of the pancreatic tissue, which in turn enhances oncogenic KRAS signaling (29).…”
Section: Microenvironmentmentioning
confidence: 99%